Studi kritis model perjanjian mudarabah pada perbankan syariah di Indonesia - Muhammad Sjaiful (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2015)
The presence of Islamic Banking in Indonesia on the one hand it should be welcomed because it is aproof of the excitement of the majority of Muslims in the country to attempt to practice the teachingsof Islam in the life of the muamalah each other. But very unfortunate if the concept of Islamic Bankingis still graft the principles of usury-based conventional banks. As shown in the mudaraba agreementscheme practiced by some Islamic Bank is still causing some problems from the viewpoint of Sharia,including Islamic Banking legal standing as related parties in the mudaraba agreement itself, the dualstatus, on the one side and the other side as mud}arib as s}ahib al mal. Held dual status that Islamic Bankingcourse diametrically opposed to the principles of sharia. Another serious problem that was seized inMud}arabah current agreement scheme is a scheme which is essentially an agreement contract debtsbetween Islamic Bank is positioning itself as a cahib al-mal with customers who position themselves asmud}arib. Being stuck mud}arabah made Islamic Bank debts into the scheme of course is very dangerousfrom the point of view of sharia because it would trap the usury-based parties in the transaction. For thereconstruction of the model that needs to be done mudaraba agreement on Islamic banking thatmodels the agreement actually purely on the basis of pure sharia upright.